Gridded bathymetry from multibeam echosounder EM120 data of the cruise M72/2 (2007) - Wintersteller, Paul; dos Santos Ferreira, Christian (PANGAEA, 2016)
Bathymetry based on data recorded during M72-2 between 23.02.2007 and 13.03.2007 in the Black Sea. The main focus of the cruise was to study the fluxes and turnover of methane and sulphur in the Black Sea hydrocarbon seep systems and investigating the microbial diversity in two contrasting permanently anoxic settings associated with fluid flow and gas seepage: the methane seeps at the shelf break of the Palaeo-Dnepr area and the hydrocarbon seeps of the mud volcanoes in the 2000 m deep Sorokin trough east of Crimea.
Keywords: Bathymetry; DTM; MBES